BIO-EFFICACY OF TEBUCONAZOLE 060 FS (RAXIL 060 FS) AS SEED TREATMENT AGAINST KARNAL BUNT, LOOSE SMUT AND FLAG SMUT OF WHEAT - BIJENDER KUMAR, (The Bioscan, 2024)
A new molecule tebuconazole 060 FS (Raxil 060 FS) was evaluated against Karnal bunt, loose smut and flag smut diseases of wheat. The results revealed that seed treatment with tebuconazole 060 FS @ 0.333/ kg seed was found to be the best, recorded lowest incidence of loose smut (0.03% smutted tillers and 0.09% infected plants) and highest disease control (96.94 per cent on tiller basis and 94.67 per cent on plant basis). It also provided highest (13.42 per cent) increase in grain yield in case of variety UP 2338 and 8.88 per cent in case of variety HD 2329. The test fungicide tebuconazole 060FS @ 0.333ml/kg seed also improved field emergence (89.73 as compared to 88.15 per cent in control). Moreover, no phytotoxicity symptoms were observed due to any fungicides treatments. None of the fungicidal seed treatment was effective in managing the Karnal bunt. However, no inference can be drawn for flag smut as the disease did not occur during both the seasons. Hence, seed treatment with tebuconazole 060 FS @ 0.333 ml/kg seed can be recommended as an alternate molecule to existing fungicides for effective management of loose smut diseases of wheat.